Analysis of Factors Influencing Visitors' Disaster Awareness in Disaster-prone Destinations in West Nusa Tenggara Province - Mahmudah Budiatiningsih; Adhitya Bagus Singandaru; Baiq Nikmatul Ulya; Hasnia Minanda; Lia Mariana (Jurnal Penelitian Pariwisata, 2026)
This study aims to analyze the factors influencing disaster awareness among visitors of disaster-prone tourist destinations in West Nusa Tenggara (NTB) Province. The method was multiple linear regression analysis involving 200 respondents, with two main dimensions as the independent variables: Psychological factors (X1), which include risk perception, disaster experience, and trust in authorities, and Environmental & Information factors (X2), which include access to information, the availability of disaster management systems, and media influence. The results showed that both factors partially and simultaneously enhance disaster awareness. Psychological factors have a dominant influence compared to environmental & information factors. These findings also showed that the combination of psychological, environmental, and information factors moderately predict variation in disaster awareness. These findings deliver theoretical and practical contributions. Theoretically, the study proposes an integrated disaster awareness model, highlighting the synergistic interplay between psychological and informational factors. Practically, the results advocate for a multidimensional strategy, urging stakeholders to combine initiatives that boost risk perception, improve risk communication, and utilize media support. Consequently, this study provides a valuable framework and concrete insights for formulating effective disaster resilience programs in the disaster-prone destinations of NTB. Keywords: disaster awareness, disaster-prone destinations, environmental & information factors, psychological factors, visitor